2015
DOI: 10.1007/s10661-015-4807-9
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of soil, medicinal, and fodder plants with lead and cadmium present in mine-affected areas, Northern Pakistan

Abstract: This study aimed to investigate the lead (Pb) and cadmium (Cd) concentrations in the soil and plants (medicinal and fodder) grown in chromite mining-affected areas, Northern Pakistan. Soil and plant samples were collected and analyzed for Pb and Cd concentrations using atomic absorption spectrometer. Soil pollution load indices (PLIs) were greater than 2 for both Cd and Pb, indicating high level of contamination in the study area. Furthermore, Cd concentrations in the soil surrounding the mining sites exceeded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 38 publications
2
16
1
Order By: Relevance
“…Et Kit. was reported having certain ability to extract HM from contaminated soil in previous research [ 54 ]. Its AG content, BCF and TF of Cd were 3.33 ± 0.55 mg·kg −1 , 0.69 and 1.25 in the soil with Cd concentration of 4.76 ± 1.2 mg·kg −1 at a mine-affect area, which did not meet the requirement for phytoextractor due to the low BCF.…”
Section: Resultsmentioning
confidence: 99%
“…Et Kit. was reported having certain ability to extract HM from contaminated soil in previous research [ 54 ]. Its AG content, BCF and TF of Cd were 3.33 ± 0.55 mg·kg −1 , 0.69 and 1.25 in the soil with Cd concentration of 4.76 ± 1.2 mg·kg −1 at a mine-affect area, which did not meet the requirement for phytoextractor due to the low BCF.…”
Section: Resultsmentioning
confidence: 99%
“…21 Mining-impacted soils and industrially impacted soils are among the poorly structured soils and generally abundant with a toxic substance such as PAHs. 22 Research on the PAHs in soil inuenced by the sole factor of mining activity or industrial activity is abundant. However, soils affected by these two different activities were generally separately researched.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, numerous studies showed high PTEs concentrations in the surrounding mining areas and ore deposits as well as in terrestrial ecosystems (Rashed 2010). and groundwater variables were influenced by the common geogenic or anthropogenic sources in the study area, that could be resulted from mafic and ultramafic rocks deposits and mining wastes, releasing high levels of PTEs to the environment (Nawab et al 2015), as well as open dumping and mobilization of mining wastes in abandoned mines, and tailing ponds could be another reason, lead to contaminate the surrounding local soils, surface rivers water and groundwater with PTEs (Shen et al 2019). The results of these correlation analysis of major ions in present study showed similarity with the previous studies, conducted by and Santana et al (2020).…”
Section: Discussionmentioning
confidence: 91%